O sentido na vida em pessoas vivendo com HIV/AIDS. - Pontes, Alisson de Meneses (2020)
Acquired Immunodeficiency Syndrome (AIDS) can be understood as a disease caused by the Human Immunodeficiency Virus (HIV), which, by infecting the human body, causes a drastic reduction in the functioning of the immune system. Since the first cases were reported more than 35 years ago, 78 million people were infected with HIV and 35 million died from AIDSrelated illnesses. In this context, Brazil occupies a prominent position with 830,000 cases. HIV infection, in addition to what has been said, is still associated with intense suffering. That is why depression has an incidence of about two to four times higher in this population and suicide rates are about 3 times higher than the general population, reflecting the loss of meaning for life in the face of illness itself. In view of this reality, the general objective of the present thesis was to propose subsidies to think policies / actions of prevention and health promotion, considering the meaning in life for PLWHA. As specific, we sought to: assess the relationship between meaning in life and suicide in people with HIV / AIDS; make a survey on the state of the art, studies that address the meaning in life in people with HIV / AIDS; investigate how the positive diagnosis for HIV / AIDS, affects in the sense of the life of the carrier; understand how meaning in life influences the mental health of people living with HIV / AIDS; to study the relationship between meaning in life and adherence to antiretroviral treatment; develop a program of promotion of meaning for life for PLWHA through a group intervention based on Logotherapy. To achieve these objectives, four articles were constructed, two theoretical and two empirical. The first presented a theoretical review on suicide from a logoterapeutic perspective. The second carried out a survey about the research that approaches the meaning in life, in the light of Logotherapy, in the context of HIV / AIDS, through a systematic review of the literature. Article III carried out a correlation study between life meaning and suicide in a group of 112 people living with HIV / AIDS. The results pointed to the strong correlation between the "realization of meaning" factor and aspects such as "positive affects", a better view of temporality, more "attraction to life" and less "attraction to death" or "repulsion to life". These studies endorsed the need to deepen the studies on the meaning in life as a preventive factor to suicide in PLWHA. From this perspective, the fourth article entitled "Living Choices: A Program to promote meaning for life in people with HIV / AIDS" was developed, based on the three axes of prevention: Universal, Selective and Indicated. In Universal was carried out an advertising campaign that objectified the promotion of sense for the life; The Selective promoted a training for more than 200 professionals from more than 23 different areas of action on suicide from a view of11 the Logoterapia; Finally, the Indicated that carried out a study of a pre-test and post-test type, with a quantitative and qualitative data approach, through a group intervention based on Logotherapy and Existential Analysis, aiming at the creation of a promotion program of meaning for life in the context of HIV / AIDS. In order to do so, we used logoterapeutic instruments, such as the Pizza of the senses and the autobiography, as well as an interview and a set of 4 scales (Multi-Judicial Scale of Suicide Tendency, Life Sense Questionnaire, Time Ontological Perception Scale, and Questionnaire Sense of Life). The sample consisted of 3 people living with HIV / AIDS and the program was executed in 8 meetings. The results of the pre-test and the post-test with the scales pointed to improvements in factor averages, such as meaningfulness, positive affects, and decrease of factors such as repulsion to life and attraction to death. These results corroborated with the Analysis of similitude and the cloud of words from the autobiographies through Iramuteq software, which evaluated the process. It is considered that the objectives were achieved, because the intervention allowed for an increase of freedom and the awakening of responsibility, awareness, the resolution of existential dilemmas, the facilitation of self-indulgence and self-transcendence. Finally, we conceive that the Escolho viver program, in its three axes of prevention, stands as a tool for social and personal transformation, seeking to promote not only suicide prevention but, above all, health promotion in its broad, as Frankl (1990) proposes, which is the development of being in its essence and sense, a way of living free, responsible, supportive and happy